Comparison of Dexmedetomidine Plus Ketamine Combination with Dexmedetomidine Plus Propofol for Awake Fiberoptic Nasotracheal Intubation: A Prospective Randomised and Controlled Clinical Trial - Kaur, Balwinder; Garg, Anubha; Kumar, Parmod; Yadav, Dr. Nisha (International Journal of Innovative Research in Medical Science, 2019)
Background: Awake fibre optic intubation (AFOI) is a valuable technique in securing the airway in predicted difficult intubation scenario, compromised airway, airway pathology, when neck extension is to be avoided, vertebral artery insufficiency, Arnold Chiari malformation, limited mouth opening as in temporomandibular joint disease, mandibular-maxillary fixation and severe facial burns.[1] Fiberoptic intubation is the best, easiest and most successful method for awake intubation. Materials and Methods: A prospective, comparative and randomized study was conducted on 100 patients undergoing elective surgery under general anaesthesia. Patients were randomly divided into two groups of 50 each. Group-DK and group-DP patient received IV dexmedetomidine 1µg/kg over 10 mins. Upon completion of the dexmedetomidine bolus, preoxygenation was done with 100% oxygen via face mask with Bain’s circuit. Group-DK patients received ketamine 0.25 mg/kg IV and Group-DP patients received propofol 1mg/kg IV so as to achieve an adequate level of sedation i.e. Ramsay sedation scale=3. Haemodynamic parameters (heart rate, systolic and diastolic blood pressure, mean arterial pressure), SpO2, EtCO2, total comfort scale and patient’s tolerance were assessed during preoxygenation, fiberscope insertion and endotracheal intubation. Results: Statistically significant difference (p<0.05) between two groups in terms of HR, SBP, DBP, MAP, total comfort score and patient tolerance was seen during fiberscope insertion and endotracheal intubation. Conclusion: Dexmedetomidine (1µg/kg) plus ketamine (0.25mg/kg) and dexmedetomidine (1µg/kg) plus propofol (1mg/kg) are safe and effective in patients undergoing fibre optic nasotracheal intubation offering conscious sedation. There is better tolerance and comfort while maintaining oxygen saturation without any hemodynamic alteration in dexmedetomidine (1µg/kg) plus ketamine (0.25mg/kg) group while on the other side use of dexmedetomidine (1µg/kg) and propofol(1mg/kg) during fibre optic intubation causing statistically significant decrease in heart rate, blood pressure, SpO2 and provides less tolerance and comfort.